O trabalhador 60+: um estudo sobre vivências e experiências relacionadas ao trabalho em uma universidade federal - Ramirez, Tiago Bruno (Universidade Federal de São Carlos, 2026)
This dissertation, titled “Workers Aged 60 and Over: A Study of Work-Related Experiences at a Federal University,” investigates aging in the workplace within the context of a federal institution of higher education, in an environment marked by organizational and technological changes. The study aimed to understand the perceptions, experiences, and challenges faced by technical and administrative staff in education (TAEs) aged 60 or older who are currently employed at the Federal University of Mato Grosso (UFMT), as well as to develop a technological tool designed to promote quality of life at work and support preparation for retirement. This is a qualitative study based on semi-structured interviews with nine TAEs, aged between 59 and 74, representing different occupational profiles, with long institutional careers and varying relationships to retirement. The results were organized into two complementary analytical levels: a thematic axis, structured around the dimensions of the interview guide, and a cross-cutting axis, focused on identifying patterns, tensions, and dynamics that permeate the participants’ daily work lives. The findings indicate a strong sense of belonging and identification with work at UFMT, coexisting with experiences of burnout, institutional pressures, and changes in interpersonal relationships. The digitization of work emerges as an ambivalent experience, perceived simultaneously as a factor in the modernization of routines and as a source of pressure, associated with the need for continuous updating, job insecurity, and the acceleration of work. We also observe an intensification of activities resulting from increased bureaucratization, control, and deadline-related demands, with repercussions on workers’ overload and burnout. The cross-sectional analysis shows that training is perceived as a structural need and that the discontinuity of institutional support measures undermines the processes of adaptation, recognition, and engagement. The results indicate that the experiences of TAEs aged 60 and older at UFMT cannot be explained exclusively by individual or age-related factors, but must be understood in light of the organizational transformations that are reshaping the criteria for valuation, recognition, and job retention in the university context. As a contribution, this study offers an in-depth analysis of the work experiences of TAEs aged 60+ at a federal public university and provides a basis for proposing a technological intervention tool aligned with the needs identified among the study’s participants.
Workers 60+: a study of work-related experiences at a federal university
Keywords: envelhecimento no trabalho; servidores técnico-administrativos em educação; transformação digital; etarismo; aposentadoria; instituições federais de ensino superior; aging in the workplace; technical and administrative staff in education; digital transformation; ageism; retirement; federal institutions of higher education; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ADMINISTRACAO DE PESSOAL; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS; 4. Educação de Qualidade; 8. Trabalho Decente e Crescimento Econômico; 10. Redução das Desigualdades